Autonomy and democracy in the theories of Max Weber and Cornelius Castoriadis - D. V. Kataev (Vestnik Moskovskogo Universiteta: Seriâ 18, Sociologiâ i Politologiâ, 2015)
Realization of Weber’s research program, its further development and application is one of the main objectives of neo- and post-Weberianism. This article is devoted to the analysis of interrelation of views of Max Weber and Cornelius Castoriadis on problems of an autonomy, bureaucracy and democracy in the light of an explication of Weber’s research program in methodological and ontological aspects. Problems of a representativeness of democracy in the conditions of bureaucratization and oligarchization are considered.